Sound source localization for circular arrays of directional microphones - Rui, Yong; Florencio, Dinei; Lam, Warren; Su, Jinyan (ICASSP, 2005)
Previous research in sound source localization has helped increase the robustness of estimates to noise and reverberation. Circular arrays are of particular interest for a number of scenarios, particularly because they can be placed in the center of the sources. First, that improves the sound capture due to the reduced distance. Second, it helps on the direction estimation, not only because of the reduced distance, but also because it increases the angle differences. Nevertheless, most research on circular arrays focused on the case of omni-directional microphones. In this paper we present a new algorithm for sound source localization developed specifically for directional microphones. Results obtained from real meeting room setups show a typical error of less than 3 degrees.